The Terrorism Death Penalty Controversy in Indonesia from the Perspective of Law and Human Rights - Ikhlashul Amal Kharisma; Deni Setiyawan (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2025)
This study aims to critically analyze the application of the death penalty for terrorism-related crimes in Indonesia from the perspectives of criminal law and human rights. The primary focus is to assess whether capital punishment can be justified as a proportionate law enforcement instrument while remaining consistent with the protection of the right to life as a non-derogable right. This research employs a normative juridical method, utilizing statutory, case-based, and conceptual approaches to examine national legal provisions, judicial decisions, and contemporary theories of punishment in conjunction with international human rights standards. The findings indicate that the death penalty retains juridical legitimacy within Indonesia's positive legal system, particularly following the enactment of Law No. 1 of 2023 on the Criminal Code, which introduces a conditional death penalty framework. Nevertheless, the justification of capital punishment based on deterrence theory lacks strong empirical support and raises serious concerns regarding proportionality and the protection of the right to life. This study recommends that the death penalty be strictly positioned as an ultimum remedium, applied in a highly selective manner with rigorous due process guarantees, and complemented by non-penal counterterrorism strategies emphasizing prevention, deradicalization, and a more humane justice-oriented approach.